Earthquake preparedness of UM Digos College: An assessment - Dela Cruz, Henry James; Garcia, Cherimie; Villanueva, Leelen; Quillip Jr., Hipolito (UM Digos Research Journal, 2017)
The study aims to assess the earthquake preparedness of the University of Mindanao, Digos College (UMDC) with regards to preparedness strategy, policy, and plan, warning capabilities, readiness to response, and emergency services and stand-by arrangements. It employed a descriptive research design conducted at the University of Mindanao, Digos College with a standardized questionnaire adapted from the City Government of Digos City Disaster Risk Reduction and Management Council (CDRRMC) Earthquake Drill Evaluation Form. Findings reveal that crouch and tuck head method was always practiced by the respondents and further consider it as an essential part of an earthquake preparedness drill, has high priority with the alarm system although evacuation routes further provided, readiness to response occur almost every time, and emergency services and stand-by arrangements had provided various teams.